IDENTIFIKASI ZAT WARNA DARI PENCAMPURAN EKSTRAK DAUN, BUNGA, DAN BUAH TUMBUHAN TROPIS SEBAGAI BAHAN SENSITIZER PADA DYE SENSITIZED SOLAR CELL - Munandar, Aris; Iswadi, Iswadi; Fuadi, Nurul (JFT : Jurnal Fisika dan Terapannya, 2017)
Research on Identification of Color Substance from Tropical Leaf Extract, Tropical Fruit and Flower Preparation as Sensitizer Material on Dye Sensitized Solar Cell, which aims to know the absorption wavelength on mixing of leaf extract, fruits and tropical flower plant as sensitizer material on Dye Sensitized Solar Cell (DSSC) and to determine the value of constituent elements contained in the mixing of leaf extracts, fruits and flowers of tropical plants as a sensitizer material in Dye Sensitized Solar Cell (DSSC). The method used in this research is direct meseration method to obtain extract from tropical plants. The result of the research shows that the highest peak is in absorbance and wavelength, in mixing flower of girlfriend of water and leaves of nail girlfriend with wavelength 232.00 nm with absorbance value 4,157, XRF test obtained element or composition of the highest in mixing sample of White Water Flower and Leaf Flower Soursop namely Potassium (K) with a value of 53.18 % can be concluded that there are some tropical plants that can be used as a dye for the manufacture of Dye Sensitized Solar Cell (DSSC).